2020
DOI: 10.1126/science.abb4808
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic bases for a potent HIV-1 capsid inhibitor

Abstract: The potent HIV-1 capsid inhibitor GS-6207 is an investigational principal component of long-acting antiretroviral therapy. We found that GS-6207 inhibits HIV-1 by stabilizing and thereby preventing functional disassembly of the capsid shell in infected cells. X-ray crystallography, cryo–electron microscopy, and hydrogen-deuterium exchange experiments revealed that GS-6207 tightly binds two ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 57 publications
9
150
2
Order By: Relevance
“…10f ). Recent reports 34 , 35 have demonstrated that an experimental long-acting HIV-1 CA inhibitor, GS-6207 (Lenacapavir, Gilead Sciences), targets the same hydrophobic cavity. Therefore, future studies are warranted to elucidate how GS-6207 affects Sec24C interactions with incoming HIV-1 cores in the cytoplasm of infected cells.…”
mentioning
confidence: 99%
“…10f ). Recent reports 34 , 35 have demonstrated that an experimental long-acting HIV-1 CA inhibitor, GS-6207 (Lenacapavir, Gilead Sciences), targets the same hydrophobic cavity. Therefore, future studies are warranted to elucidate how GS-6207 affects Sec24C interactions with incoming HIV-1 cores in the cytoplasm of infected cells.…”
mentioning
confidence: 99%
“…Nup153 and CPSF6 bind to a conserved hydrophobic binding pocket in the CA NTD, involving α-helices 3 and 4 [ 45 , 46 , 47 , 117 ]. This pocket also binds the antiretroviral small molecules PF74 [ 46 , 119 ], BI-2 [ 46 ], and GS-6207 [ 120 , 121 ]. The CA mutations N74D and A77V disrupt this binding pocket and are widely used to study the function of these host factors.…”
Section: Host Factors That Interact With Hiv-1 Ca Around the Nuclear Pore Complexmentioning
confidence: 99%
“…This is not good news for the virus, and this viral weakness selects the viral capsid as an exceptional target for a new class of drugs. A recent compound, called Lenacapavir, interferes with the binding of Nup153 and CPSF6 to in vitro assembled cores, stabilizing them [ 140 ]. Thus, Lenacapavir is a first-in-class HIV-1 capsid inhibitor with potent antiviral activity against both wild-type virus and resistant mutants to current antiretroviral agents.…”
Section: Hivmentioning
confidence: 99%